Autoantibodies to estrogen receptor α in systemic sclerosis (SSc) as pathogenetic determinants and markers of progression. - Antonello Giovannetti (Public Library of Science (PLoS), 2013)
Systemic sclerosis (SSc) is a multisystem autoimmune disease of unknown etiology characterized by inflammation, autoantibody production, and fibrosis. It predominantly affects women, this suggesting that female sex hormones such as estrogens may play a role in disease pathogenesis. However, up to date, the role of estrogens in SSc has been scarcely explored. The activity of estrogens is mediated either by transcription activity of the intracellular estrogen receptors (ER), ERα and ERβ, or by membrane-associated ER. Since the presence of autoantibodies to ERα and their role as estrogen agonists interfering with T lymphocyte homeostasis were demonstrated in other autoimmune diseases, we wanted to ascertain whether anti-ERα antibodies were detectable in sera from patients with SSc. We detected anti-ERα antibody serum immunoreactivity in 42% of patients with SSc (30 out of 71 analyzed). Importantly, a significant association was found between anti-ERα antibody values and key clinical parameters of disease activity and severity. Fittingly, anti-ERα antibody levels were also significantly associated with alterations of immunological features of SSc patients, including increased T cell apoptotic susceptibility and changes in T regulatory cells (Treg) homeostasis. In particular, the percentage of activated Treg (CD4(+)CD45RA(-) FoxP3(bright)CD25(bright)) was significantly higher in anti-ERα antibody positive patients than in anti-ERα antibody negative patients. Taken together our data clearly indicate that anti-ERα antibodies, probably via the involvement of membrane-associated ER, can represent: i) promising markers for SSc progression but, also, ii) functional modulators of the SSc patients' immune system.